Handbook of corporate finance empirical corporate finance. - Eckbo, Bjorn Espen (Handbooks in finance)
Judging by the sheer number of papers reviewed in this Handbook, the empirical analysis of firms' financing and investment decisions-empirical corporate finance-has become a dominant field in financial economics. The growing interest in everything "corporate" is fueled by a healthy combination of fundamental theoretical developments and recent widespread access to large transactional data bases. A less scientific-but nevertheless important-source of inspiration is a growing awareness of the important social implications of corporate behavior and governance. This Handbook takes stock of the mai.